Against fascism, for racial equality: communists, anti-racism and the road to the Second World War in Australia, South Africa and the United States. (20th October 2017) - Smith, Evan
Abstract: The Second World War (after June 1941) was a high point for the international communist movement with the Popular Front against fascism bringing many new people into Communist Parties in the global West. In the United States, South Africa and Australia, the Communist Party supported the war effort believing that the war against fascism would eventually become a war against imperialism and capitalism. Part of this support for the war effort was the support of black and indigenous soldiers in the armed forces. This activism fit into a wider tradition of these communist parties' anti-racist campaigning that had existed since the 1920s. This article looks at how support for the national war effort and anti-racist activism intertwined for these CPs during the war and the problems over 'loyalty' and commitment to the anti-imperial struggle that this entanglement of aims produced.